PENGARUH PUPUK ORGANIK CAIR DAN PUPUK MAJEMUK NPK TERHADAP PERTUMBUHAN SETEK BATANG CINCAU HIJAU: Effect of Liquid Organic Fertilizer and NPK Compound Fertilizer On The Growth of Green Grass Cincau (Premna oblongifolia Merr) Stem Cuttings in Peat Soil - Agung Prasetyo; Sih Winarti; Siti Zubaidah; Yustinus Sulistiyanto; Hastin Ernawati Nur Chusnul Chotimah (AgriPeat, 2022)
This study was to determine the effect of NPK and liquid organic fertilizers and the interaction on the growth of green grass jelly stem cuttings on peat soil. The research was carried out in September - December 2020, located in the plastic house of the Experimental Garden Installation Department of Agricultural Cultivation, Faculty of Agriculture, University of Palangka Raya. This experiment used a factorial completely randomized design (CRD) consisting of 2 (two) treatment factors with 3 (three) replications. The first factor was the concentration of POC administration consisting of 4 (four) levels (0, 3, 6 and 9 mL of POC L-1 water) and the second factor is the dose of NPK 15: 15: 15 fertilizer consisting of 4 (four) levels ( 0, 1, 2 and 3 g NPK polybag-1). The results showed that there was an interaction between the administration of 3 mL POC L-1 water and 3 g NPK polybag-1 on shoot length (77.57 cm) and the treatment of 9 mL POC L-1 water and 3 g NPK polybag-1 on weight. fresh leaves (53.83 g). A single factor of 3 g NPK polybag-1 fertilizer was able to give a significant effect on the number of shoots (4.58 pieces), shoot length (75.31 cm), number of leaves (38.33 strands), leaf area (3032.77 cm2), heavy fresh leaves (54.86 g) root length (30.99 cm) and root volume (7.00 cm-3). The provision of 9 mL of POC L-1 water gave a significant effect on the number of roots in the treatment (10.58 fruit) and root weight in the treatment of 9 mL of POC L-1 water (2.39 g)